Weak water absorption lines around 1.455 and 1.66 μm by CW-CRDS; Journal of Molecular Spectroscopy; Vol. 244, № 2 - Mikhailenko S. N. Semen Nikolaevich; Wang G.; Kassi S.; Campargue A. (2007, 2007)
Title screen